2015
DOI: 10.1002/2014gl062956
|View full text |Cite
|
Sign up to set email alerts
|

Compounding effects of warm sea surface temperature and reduced sea ice on the extreme circulation over the extratropical North Pacific and North America during the 2013–2014 boreal winter

Abstract: Unprecedented atmospheric circulations with extreme weather were observed in the extratropical Northern Hemisphere during the winter of 2013-2014. The anomalous circulations were the manifestation of the Pacific pattern or the North Pacific Oscillation/Western Pacific pattern but with extremely large amplitude. Simulation results suggest that the anomalous atmospheric circulations were constructively induced by anomalous sea surface temperature in the tropical Pacific and extratropical North Pacific, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 14 publications
(18 reference statements)
8
143
1
Order By: Relevance
“…Previous studies have suggested the TNH (or TNH-like) pattern may be triggered by tropical forcing mechanisms, such as the El Niño (Mo and Livezey 1986;Barnston et al 1991;Yu et al 2012;Yu and Kim 2011;Yu and Zou 2013;Zou et al 2014), the quasi-biennial oscillation (Barnston et al 1991), the propagation of the wave activity initiated from the western tropical Pacific Ocean (Wang Lee et al 2015;Seager and Henderson 2016;Hu et al 2017), and the internal dynamics in the atmosphere (Kumar et al 2013;Seager et al 2014;Xie and Zhang 2017). Also, recent warming in the Arctic regions has been suggested to exert strong impacts on midlatitude weather and climate by altering large-scale atmospheric circulation patterns (Cohen et al 2012(Cohen et al , 2014Kim et al 2014;Peings and Magnusdottir 2014;Deser et al 2015;Lee et al 2015;Overland et al 2015Overland et al , 2016Yu et al 2017). Thus, forcing related to certain tropical Pacific Ocean or polar conditions may be potential factors for the phase-locking of the TNH pattern.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous studies have suggested the TNH (or TNH-like) pattern may be triggered by tropical forcing mechanisms, such as the El Niño (Mo and Livezey 1986;Barnston et al 1991;Yu et al 2012;Yu and Kim 2011;Yu and Zou 2013;Zou et al 2014), the quasi-biennial oscillation (Barnston et al 1991), the propagation of the wave activity initiated from the western tropical Pacific Ocean (Wang Lee et al 2015;Seager and Henderson 2016;Hu et al 2017), and the internal dynamics in the atmosphere (Kumar et al 2013;Seager et al 2014;Xie and Zhang 2017). Also, recent warming in the Arctic regions has been suggested to exert strong impacts on midlatitude weather and climate by altering large-scale atmospheric circulation patterns (Cohen et al 2012(Cohen et al , 2014Kim et al 2014;Peings and Magnusdottir 2014;Deser et al 2015;Lee et al 2015;Overland et al 2015Overland et al , 2016Yu et al 2017). Thus, forcing related to certain tropical Pacific Ocean or polar conditions may be potential factors for the phase-locking of the TNH pattern.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The amplified pattern is associated with an increase in the Greenland blocking index and a tendency for persistent ridge-trough jet stream configuration upstream of Greenland (North America) as well as downstream (Europe). While changing SST patterns in midlatitude oceans also influence jet stream configurations, interannual variability in regional locations of substantial sea ice loss in the previous seven years may have reinforced the position and persistence of height anomalies at midlevels, which in turn affects the location of anomalous ridges and troughs (Lee et al 2015). Thus, highly regional loss of sea ice (e.g., BK and Baffin-Hudson Bay) is important to linkages, rather than an Arctic-wide zonal influence.…”
Section: The Influence Of Greenland On Eastern Northmentioning
confidence: 99%
“…The topic, however, is consequential and a major science challenge, as continued Arctic changes are an inevitable aspect of anthropogenic global change (Jeffries et al 2013) and may be an opportunity for improved extended-range forecasts at midlatitudes (Walsh 2014). An intriguing question is whether recent extreme weather-such as the cold eastern U.S. winters of /10, 2010/11, January 2014, and November 2014-February 2015; record floods in the United Kingdom in 2007, 2012, and 2013/14; and cold outbreaks in eastern Asia-were merely random events or were related to recent global or Arctic climate change (e.g., Jaiser et al 2012;Tang et al 2013;Wallace et al 2014;Kim et al 2014;Mori et al 2014;Cohen et al 2014;Feldstein and Lee 2014;Lee et al 2015;Barnes and Screen 2015). There is also the potential for midlatitude (e.g., Sato et al 2014;Perlwitz et al 2015) and tropical (e.g., Ding et al 2014) variability to affect the Arctic, further complicating the story.…”
Section: Introductionmentioning
confidence: 99%
“…Arctic warming over the Barents and Kara seas and its impacts on the mid-latitude circulations have been widely discussed (Dobricic et al, 2016;Semenov and Latif, 2015;Kug et al, 2015;Sato et al, 2014). Another particular regional warm core (Screen and Simmonds, 2010) is the East Siberian and Chukchi seas, which is related to severe winters over North America (Kug et al, 2015;Lee et al, 2015). Screen and Simmonds (2010) also described the third particular regional warm core -northeast Canada and Greenlandwhich has been less investigated.…”
Section: Introductionmentioning
confidence: 99%